Chapter Aspektualität im Resianischen und die Rolle des Sprachkontakts - Pila, Malinka (Biblioteca di Studi Slavistici, 2023)
This study deals with aspectuality in Resian, a Slovene-based variety of north-eastern Italy, and the probable role of Romance influence on developments in this domain. In part, these findings are compared with the situation found with other non-Romance linguistic varieties spoken in Italy, especially Molise Slavic. The functional-semantic field of aspectuality is considered both in relation to its grammatical centre, viz. verbal aspect, and its lexical periphery. Language contact plays an important role in the almost complete transition of the Resian dual aspect system to a purely derivational opposition "imperfective : perfective", also absorbing most of its prior morphosyntactic opposition "imperfect : aorist : perfect". Furthermore, the special aspectual selection properties of phasal verbs and the role of aspect in the functions of modal verbs merit particular mention in this respect. In the case of lexical and periphrastic means of expression, a number of calqued progressive and prospective (imminent) periphrases, mostly calqued from Romance models, are discussed.